Simulation Freezing and Defrosting Processes on Solid Surfaces - Vo, Chi Chinh; Vu, Huy Khue (Engineering and Technology For Sustainable Development, 2024)
Freezing ice on round or flat pipe surfaces is a common challenge in refrigeration systems, including ice heat storage tanks for air conditioning systems, ice molds for tree ice machines, flake ice machines, cube ice machines, and so on. As a result, calculating and establishing the relationship between the thickness of the created rock layer and the freezing time is critical for proper arranging the heat exchange tubes, defining the size of the heat exchanger tubes, and selecting an acceptable stone mold size. This article demonstrated the simulation of the ice-freezing process on the surfaces of pipes and flat surfaces, as well as the defrosting process on those surfaces. The simulation results show that, after a freezing time of about 10 hours, the thickness of the ice layer formed on cylindrical surfaces and flat surfaces is about 50 mm and 80 mm, respectively. The formation of ice on flat surfaces is better than in round one. In addition, the defrosting process is faster than the freezing process. The results also help engineers have a basis for choosing the freezing time to operate the refrigeration system safely, avoiding liquid flooding at the end of the operation process. Also, these results can be applied to ice production or ice storage for air conditioning.